FASN promotes the stemness of cancer stem cells and protects colorectal cancer cells from ferroptosis by inhibiting the activation of SREBP2 - Ming Wang; Fulin Ge; Cheng Wu; Binbin Su; Xiaoyu Dong; Shiping Xu; Hui Shi (Frontiers in Immunology)
IntroductionFatty acid synthase (FASN) is a key regulator of lipid metabolism, but its role in colorectal cancer (CRC) stemness and ferroptosis remains unclear.MethodsFASN expression in CRC was analyzed using TCGA data and validated in CRC cell lines (CACO-2, HCT116, SW480) and normal HIEC-6 cells via qRT-PCR and Western blot. HCT116 cells (highest FASN expression) were used for experiments. FASN silencing (shRNA) effects on CSCs were assessed via 3D spheroid formation and CD133+CD44+ flow cytometry. In vivo tumor growth was tested in BALB/c nude mice. Mechanistic assays included cholesterol detection, SREBP2 Western blot, fatostatin rescue experiments, ferroptosis markers (ferrous ions, ROS, MDA, 4-HNE, mitochondrial function), and FASN-SREBP2 co-immunoprecipitation.ResultsFASN was overexpressed in CRC tissues (TCGA) and cell lines, with highest levels in HCT116. It was upregulated in 3D spheroids and CD133+CD44+ CSCs. FASN silencing reduced spheroid formation, in vivo tumor growth, and CD133+CD44+ cells. Mechanistically, FASN knockdown decreased cholesterol, activated SREBP2, and induced ferroptosis (elevated ferrous ions, ROS, lipid peroxidation, mitochondrial dysfunction); these effects were reversed by fatostatin. Co-IP confirmed FASN-SREBP2 interaction.DiscussionFASN promotes CRC progression by enhancing CSC stemness and suppressing ferroptosis through SREBP2 inhibition, highlighting its potential as a therapeutic target.